MORPHOLOGICAL VARIATIONS OF SUMATRAN TORENT FROGS, Huia sumatrana (Yang, 1991) AND H. modiglianii Doria, Salvidio and Tavan, 1999 - Hellen - Kurniati (Masyarakat Zoologi Indonesia, 2009)
Kurniati, H. 2009. Morphological variations of Sumatran Toren frogs, Huiasumatrana (Yang, 1991) and H. modiglianii Doria, Salvidio and Tavan, 1999. ZooIndonesia 18(1):9-20. Based on an examination specimens of the Sumatran TorrentFrog, Huia sumatrana in Museum Zoologicum Bogoriense (MZB), Indonesia, severalindividuals were found to possess morphological characters similar to those of H.modiglianii, including the number of crossbars on the thigh, snout morphology, anddorsal and ventral pattern and coloration. A similar degree of morphological variationin H. sumatrana that close to H. modiglianii tentatively is named as H. cf sumatrana.